Thermodynamics and self diffusion of confined fluid. (30th April 2020) - Hashemi, S
Abstract: The pressure and self diffusion of confined model fluid are being investigated using Monte Carlo NVT simulation. Different aspect ratios of contents, cavity sizes and packing fractions are presented. For these confined systems, almost the same pressures are observed in the isotropic region, in comparison with the pressure of the corresponding bulk systems and theoretical results. In the nematic region, the pressure of the bulk and the largest confined systems are almost the same and the pressures of different boxes diverge. The pressure of the confined system also shows decreasing oscillatory behaviour against cavity size for all aspect ratios. The period of these oscillations depends on the aspect ratio of the contents and is independent of the packing fraction of the system. The effect of confinement on the self diffusion of particles is also explored and creation of unstable nematic regions is revealed at the low packing fraction of 0.35.